Experimental Evidence of Chiral Ferrimagnetism in Amorphous GdCo Films. Issue 27 (23rd May 2018) - Streubel, Robert; Lambert, Charles‐Henri; Kent, Noah; Ercius, Peter; N'Diaye, Alpha T.; Ophus, Colin; Salahuddin, Sayeef; Fischer, Peter
Abstract: Inversion symmetry breaking has become a vital research area in modern magnetism with phenomena including the Rashba effect, spin Hall effect, and the Dzyaloshinskii–Moriya interaction (DMI)—a vector spin exchange. The latter one may stabilize chiral spin textures with topologically nontrivial properties, such as Skyrmions. So far, chiral spin textures have mainly been studied in helimagnets and thin ferromagnets with heavy‐element capping. Here, the concept of chirality driven by interfacial DMI is generalized to complex multicomponent systems and demonstrated on the example of chiral ferrimagnetism in amorphous GdCo films. Utilizing Lorentz microscopy and X‐ray magnetic circular dichroism spectroscopy, and tailoring thickness, capping, and rare‐earth composition, reveal that 2 nm thick GdCo films preserve ferrimagnetism and stabilize chiral domain walls. The type of chiral domain walls depends on the rare‐earth composition/saturation magnetization, enabling a possible temperature control of the intrinsic properties of ferrimagnetic domain walls. Abstract : Chiral spin textures in amorphous ferrimagnetic films are surveyed, paving the way toward a generalized understanding of (interfacial) vector‐spin‐exchange‐driven chirality selection in complex multicomponent systems. High‐resolution Lorentz microscopy reveals chiral ferrimagnetic domain walls whose type depends on the rare‐earth composition/saturation magnetization, enabling a potential temperature control of intrinsic domain wall properties.